Dynamics of Regional Government Policy - Bakri, Riani; Jeddawi, Murtir; Utami, Fadilah Reski; Husain, Muh. Fahril (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
Local autonomy, basicly is one of great issues of the unitary state. One side, maintaining unitary state of Indonesia, it’an absolute thing with sentralisation policy. But the other side, desentralisation is a need too based on Indonesian constitution. In experiences of government of Indonesia history, there were many of public policies of local autonomy have been determined. Those policies were arrange dynamic issue which being conflict each other. The public policies were emphasized main issue at that time as local autonomy legal politics, so that the content of those public policies were variously about local government.